2001
DOI: 10.1354/vp.38-6-715
|View full text |Cite
|
Sign up to set email alerts
|

Streptozocin-induced Pancreatic Islet Destruction in Beef Cows

Abstract: Abstract. Streptozocin (STZ) induces diabetes mellitus in sheep and pigs. To test the effect of STZ in cattle, cows were given 75-150 mg STZ per kilogram of body weight. Cows receiving 150 mg/kg required euthanasia within 24 hours after infusion because of the severe systemic effects of STZ. Seven cows receiving doses of Յ100 mg/kg had mild to marked decrease in islet immunoreactivity for insulin and in pancreatic islet density and mild to severe tubulointerstitial nephritis. Two cows receiving 75 and 85 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
5
2
0
Order By: Relevance
“…In the current study, STZ caused histopathological alterations in the pancreatic tissue. This was in accordance with Higdon et al (2001) who reported that STZ caused inflammatory changes in pancreatic islets of diabetic rats. Consequently, this leads to atrophy in islands of the Langerhans cells associated with vacuolation of islet cells.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, STZ caused histopathological alterations in the pancreatic tissue. This was in accordance with Higdon et al (2001) who reported that STZ caused inflammatory changes in pancreatic islets of diabetic rats. Consequently, this leads to atrophy in islands of the Langerhans cells associated with vacuolation of islet cells.…”
Section: Discussionsupporting
confidence: 93%
“…10,26) As diabetic processes, atrophy and vacuolation of islet cells according to the destruction of B cells were demonstrated in the present study by the decrease in the number of pancreatic islets observed in histomorphometry. The anti-diabetic activities of numerous herbal extracts have been observed based on the histopathology and histomorphometry of the pancreas.…”
Section: Discussionsupporting
confidence: 67%
“…In the STZ induced diabetic rats, inflammatory changes were detected in the pancreatic islets results from selectively destroy of insulin-producing B cells and consequently, atrophy and decrease of the numbers of pancreatic islets observed are induced. 10,28) As diabetic process, atrophy and vacuolation of islet cells according to destroy of B cells were demonstrated in the present study with decrease of the number of observing pancreatic islets on the histomorphometry. However, these changes are dramatically and dose-dependently inhibited by SMK001 treatment, and antidiabetic activities of numerous herbal extracts have been observed base on these histopathology and histomorphometry of the pancreas.…”
Section: Discussionsupporting
confidence: 66%